AMERICAN ENSLAVEMENT AS SEEN IN NARRATIVE OF THE LIFE OF FREDERICK DOUGLAS & IN THE INTERESTING NARRATIVE OF THE LIFE OF OLAUDAH EQUIAO - Suparman, Suparman (Universitas Muhammadiyah Surakarta, 2005)
Mimetic approach is used in this study to reveal the practice of slavery depicted in two novels